Investigation of Error Sources Measuring Deformations of Engineering Structures by Geodetic Methods - Vladislovas Česlovas Aksamitauskas; Donatas Rekus; Stasys Čirba (The Baltic Journal of Road and Bridge Engineering)
Modern bridges and road structures are characterized by large-size objects, the complexity of engineering structures and a high precision of joints and knots of structural elements. Due to the above characteristics and an extremely increased mechanization degree, construction technology and nature of the structural engineering equipment has changed, while demand for high accuracy increased. In order to carry out the measurements as accurately as possible, digital surveying devices are used. The main part of the geodetic work in structures is leveling. Using digital leveling instruments for the precise leveling, the methodology of measurements changes due to the occurrence of the specific sources of error that affect the structural engineering measurements and observations of deformations of engineering structures. For this purpose, it is necessary to perform digital precision investigations of digital levels and coded staffs of specific models, precision of digital leveling, and technical, geometric and metrological parameters of instruments.